213k views
5 votes
Rewrite
sin^25xcos^25x simplified using power reduced formulas

User DMTintner
by
4.7k points

2 Answers

3 votes

Final answer:

To simplify the expression sin^2(5x)cos^2(5x) using power reduced formulas, substitute sin^2(x) = (1-cos(2x))/2 and cos^2(x) = (1+cos(2x))/2 into the expression. The simplified expression is sin^2(10x)/4.

Step-by-step explanation:

To simplify the expression sin^2(5x)cos^2(5x) using power reduced formulas, we can use the formulas:

  • sin^2(x) = (1-cos(2x))/2
  • cos^2(x) = (1+cos(2x))/2

Substituting these formulas into the given expression, we get:

(1-cos(10x))/2 * (1+cos(10x))/2 = (1-cos^2(10x))/4 = sin^2(10x)/4

User Perfectionist
by
5.2k points
4 votes

Step-by-step explanation:

The power reducing formulas are given by the following:


\sin^2 x = (1- \cos2x)/(2)


\cos^2 x = (1+ \cos2x)/(2)

We can then write the given expression as


\sin^25x \cos^25x


= \left((1- \cos 2(5x))/(2) \right) \left((1+ \cos 2(5x))/(2) \right)


= (1)/(4)(1- \cos 10x)(1+ \cos 10x)


= (1)/(4)(1- \cos^2 10x)


= (1)/(4) \left((1- \cos 20x)/(2) \right)

or


\sin^25x \cos^25x= (1)/(8)(1- \cos 20x)

User Robinwen
by
4.5k points